Task-Based Budgeting in Environmental Projects Planning: A Case Study of a Manufacturing Company in Poland - LEPCZYŃSKA, Anna SIEMIONEK-; CHALASTRA, Michał (Journal of Environmental Management and Tourism, 2023)
In this paper most important differences between performance budgeting and traditional budgeting were presented. The aim of this paper is to focus only on selected differences. The conducted case-study in Poland reveals that activity-based budgeting is an effective method of financial management. Traditional budgeting is implemented according to older concepts. These rules are not compatible with the demands of modern budgeting. Unfortunately, the traditional budgeting method is widely used in public sector in Poland. It is also quite often used in commercial enterprises. The traditional method of budgeting is easier and quicker to implement. Thus, it is popular. On the other hand, it does not allow to achieve positive effects of activity-based budgeting.